Evaluation Study of the Working of Antyodaya Programme in Rajasthan - Planning Commission (Planning Commission, 1979)
The ANTYODAYA Programme was launched by the Government of Rajasthan on 2nd October, 1977 for the upliftment of the "poorest of the poor" families in the State by providing them in each village means of livelihood in the form of various Programmes of self-employment, wage employment and old age pension. During the year 1978-79 a provision of Rs.200.00 lakhs has been made against which the anticipated expenditure is Rs.300.00 lakhs. During the first round 1.60 lakh families were identified whereas during the second round it is anticipated that 1.40 lakh families would be benefitted.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India